Long COVID in Children and Adolescents: A Retrospective Study in a Pediatric Cohort. Issue 4 (4th January 2023) - Baptista de Lima, Joana; Salazar, Luís; Fernandes, Alexandre; Teixeira, Carla; Marques, Laura; Afonso, Caldas
Abstract : Studies on long coronavirus disease (COVID) in children are scarce. We aimed to describe persistent symptoms and identify risk factors for its development. In our study population, 17.6% presented with long COVID, with respiratory symptoms more frequent in the first weeks and neuropsychiatric symptoms over time. Chronic conditions and obesity were risk factors, and adolescents were at a greater risk for long COVID.